2020
DOI: 10.1007/s00464-020-07814-y
|View full text |Cite
|
Sign up to set email alerts
|

Scarless endoscopic thyroidectomy (SET) lateral neck dissection for papillary thyroid carcinoma through breast approach: 10 years of experience

Abstract: Background Breast approach endoscopic thyroidectomy with lateral neck lymph node metastases dissection has been described. However, in this article, we report on 10 years' experience with the breast approach to patients with endoscopic thyroidectomy with level II, III, and IV lateral neck dissection (LND). Patients with papillary thyroid carcinoma (PTC) who received scarless endoscopic thyroidectomy (SET) were included to evaluate its therapeutic effect. Methods Between June 2009 and June 2019, we selected 155… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 14 publications
1
54
0
Order By: Relevance
“…Differentiated thyroid cancer (DTC) is often diagnosed postoperatively after resection of sonographic and/or cytological suspicious thyroid nodules. Since its prognosis is excellent in most cases, the main goals of surgery are, alongside with complete tumor resection, low morbidity, and satisfying cosmetic results ( 1 ). The use of prophylactic resection of clinically not involved central lymph nodes for papillary thyroid cancer (PTC), for example, is very controversial ( 2 , 3 , 4 ); it bears the risk of postoperative hypocalcemia, and radioiodine treatment (RAI) is known to treat micrometastatic disease ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiated thyroid cancer (DTC) is often diagnosed postoperatively after resection of sonographic and/or cytological suspicious thyroid nodules. Since its prognosis is excellent in most cases, the main goals of surgery are, alongside with complete tumor resection, low morbidity, and satisfying cosmetic results ( 1 ). The use of prophylactic resection of clinically not involved central lymph nodes for papillary thyroid cancer (PTC), for example, is very controversial ( 2 , 3 , 4 ); it bears the risk of postoperative hypocalcemia, and radioiodine treatment (RAI) is known to treat micrometastatic disease ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Differentiated thyroid cancer (DTC) is often diagnosed postoperatively after resection of sonographic and/or cytological suspicious thyroid nodules. Since its prognosis is excellent in most cases, main goals of surgery are, alongside with complete tumor resection, low morbidity and satisfying cosmetic results [1].…”
Section: Introductionmentioning
confidence: 99%
“…We had performed over 1200 ESTC procedures at our center before performing endoscopic selective LND. However, the mean operative time was 307.5 ± 74.4 min, which is much longer than that of open surgery [2,15]. In summary, Qin's seven steps for endoscopic selective LND via the chest approach in patients with differentiated thyroid cancer is a safe approach and achieves good cosmetic results.…”
Section: Discussionmentioning
confidence: 92%
“…Lateral neck dissection (LND) is recommended for these patients to improve the prognosis [10,11]. However, the traditional open LND necessitates a large neck incision, which has a detrimental effect on the quality of life of patients [2,[12][13][14]. A few studies have reported complete endoscopic dissection of the lateral lymph nodes [2,14,15]; however, it is a technically challenging procedure that requires surgical expertise.…”
mentioning
confidence: 99%
“…The working space is filled with CO 2 , maintaining a pressure of approximately 7 mmHg. Devices have been introduced in this kind of approach, such as U-shaped retractors, suspension sutures, ultrasonic coagulators, and minilap (31,(37)(38)(39)(40)(41)(42)(43).…”
Section: Chest-breast Approachmentioning
confidence: 99%